The Impact of Gluten and Inulin on Breath Hydrogen, Gastrointestinal Symptoms, Satiety, and Sensory Attributes in Health Adults. (14th June 2022) - Evenson, Alexa; Zwack, Codi; Stovern, Shelby; Brewer, Katie; Windsperger, Austin; Metelmann, Linnea; Rooney, Elissa; Anderson, Lydia; Meyer-Iverson, Decorah; Johnson, Grace
Abstract: Objectives: To investigate the effects of gluten and inulin on breath hydrogen, gastrointestinal (GI) symptoms, satiety, and sensory attributes in healthy individuals. Methods: A double-blind, randomized, controlled crossover design was conducted with 26 healthy adults (ages 18–39). Fasted subjects consumed a 16 oz. low FODMAP smoothie as the control. Treatment smoothies consisted of the low FODMAP base and either gluten (5g) or inulin (5g). Breath hydrogen measures were taken at baseline, 1, 2, and 3 hours. GI symptoms surveys were collected at baseline, 30 min, 1, 1.5, 2, 3, 12, and 24 hours. VAS was collected at baseline, 10 min, 30 min, 1, 1.5, 2 and 3 hours. Sensory analysis was completed after the first initial sips of smoothie consumption. Breath hydrogen, GI symptoms, and VAS scales were assessed by area under the curve using the trapezoidal rule. Repeated measures ANOVA was used to evaluate differences between treatments with P < 0.05. Results: In the sample of healthy adults, there was no difference (p > 0.05) in breath hydrogen between treatments at any time point or total AUC. There was a difference for GI symptoms between the low FODMAP control and gluten treatment, with gluten producing less total GI symptoms (mean difference 2.842; p = .015). There was no difference in any sensory attribute or overall liking between treatments. There was a difference between the control and inulin treatments for hunger (MD = −3.829; p = 0.49) and fullness (MD = 3.88; p = .044) but no difference between the control and gluten (p > .05). There were no differences between treatments for satisfaction and volume of food to eat (p > .05). Conclusions: In healthy adults, there were no differences in breath hydrogen measures between treatments. Overall, there were few GI symptom differences with gluten producing less total GI symptoms. These results support not limiting gluten or inulin consumption in healthy individuals as they did not lead to increased breath hydrogen or GI symptoms. Funding Sources: The College of Saint Benedict and Saint John's University Undergraduate Research Grant.